PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - suardi, suardi (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract: Decreased job satisfaction is expected to cause poor employee performance. The governing body is seen in general, where employees appear to carry out daily routines without the desire to improve work skills. We assess the effect of job satisfaction on employee performance. Data processing is carried out in this study using qualitative and quantitative approaches. In qualitative retrofitting, the data and information collected are described to get an empirical interpretation. While the quantitative approach uses a statistical model of regression and correlation, aims to determine the effect and form the relationship between two variables namely job satisfaction and performance variables. The results of this study indicate that employee performance is satisfactory. This is indicated by statements as much as 58.62 percent of respondents agreed with statements that stated satisfying expressions. The findings also revealed that there was a high level of job satisfaction, with an indication of 86.90 percent agreeing statements on such matters. Keywords: employee performance, satisfaction.